A method for preparing low dielectric continuous basalt fiber by raw material multi-component compounding and ceramic coating coating
Patent Information
- Application Number
- CN202611280944.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-20
AI Technical Summary
然而,该技术方案存在以下突出问题:(1)CaO和MgO含量过低,不符合天然玄武岩纤维原料的客观实际
[0035]1)显著降低介电常数: 通过确保SiO2≥52%以保障网络骨架完整性,配合Al2O3(15-18%)适中含量、CaO(4-6%)、MgO(3-5%)、CaO+MgO(7-10%)的致密网络结构,以及B2O3(2.0-5.0%)的精确控制和CeO2/Ho2O3的协同效应,介电常数(1MHz)可从普通玄武岩纤维的6.0-6.5降低至3.8-4.5。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of inorganic non-metallic materials technology, specifically relating to a method for preparing low-dielectric continuous basalt fibers by multi-component mixing of raw materials and ceramic coating. Background Technology
[0002] Continuous basalt fiber, as a novel inorganic non-metallic high-performance fiber material, possesses high strength, high modulus, high temperature resistance, acid and alkali corrosion resistance, and excellent insulation properties, showing broad application prospects in aerospace, defense, high-frequency and high-speed printed circuit boards, and 5G communications. However, basalt fibers produced by existing methods still have shortcomings in dielectric properties. Although their dielectric constant (approximately 6.0-6.5) and dielectric loss (approximately 0.010-0.015) have reached the level of E-glass fiber, they still cannot meet the stringent requirements of high-end applications such as high-frequency and high-speed printed circuit boards (PCBs) where low dielectric properties are explicitly required.
[0003] Basalt fiber is made from natural intermediate-basal igneous rock ores such as basalt, diabase, andesite, and diorite. The chemical composition of the ore determines the fiber composition, which in turn determines the fiber's basic properties. However, the composition of natural ores varies considerably. Intermediate-basal igneous rocks from different origins and strata exhibit significant differences in the content of major oxides. Their SiO2 content is typically between 45-66%, Al2O3 content between 13-18.5%, CaO content between 4-8%, MgO content between 3-11%, total alkali (Na2O+K2O) content between 3-6%, and TiO2 content between 2-4%. The total amount of CaO+MgO in natural intermediate-basal igneous rocks is generally not less than approximately 10-12%, and the total amount of alkali metal oxides is generally not less than approximately 3%. This is determined by the natural properties of intermediate-basal volcanic rocks. Meanwhile, the SiO2 content in continuous basalt fibers is usually not less than 52%, which is a basic requirement to ensure the integrity of the fiber network skeleton and spinnability.
[0004] Existing technologies (such as CN202210684757) disclose a method for preparing low-dielectric basalt fibers, which reduces the dielectric constant to 3.89-4.07 by adding large amounts of B2O3 (13-23 parts by weight) and rare earth oxides (CeO2 0.5-5.0 parts by weight, Ho2O3 0.5-5.0 parts by weight). However, this technical solution has the following prominent problems: (1) The content of CaO and MgO is too low, which does not conform to the objective reality of natural basalt fiber raw materials. In this solution, CaO is only 2.0-5.0 parts by weight, MgO is only 1.5-4.0 parts by weight, and the total content of CaO+MgO is only 3.5-9.0 parts by weight. The total amount of CaO+MgO in natural basalt fiber raw materials is generally not less than about 10-12%. The content of CaO and MgO in this solution is significantly lower than the normal range of natural basalt, which deviates from the essential characteristics of basalt fiber as a "natural raw material". (2) The low Al2O3 content leads to a loose fiber structure and severely insufficient mechanical properties. In this scheme, Al2O3 is only 6.0-13.0 parts by weight. As an important network forming agent, Al2O3 is a key component for maintaining the integrity and density of the glass network skeleton. Too low a content will significantly reduce the tensile strength and elastic modulus of the fiber. (3) The excessive B2O3 addition leads to serious environmental pollution and process problems. In this scheme, the B2O3 addition is as high as 13-23 parts by weight. A large amount of B2O3 volatilizes during the high-temperature melting process, generating boron-containing fumes, which seriously pollutes the environment and excessively damages the network structure, exacerbating the deterioration of the fiber's mechanical properties.
[0005] In order to overcome the aforementioned natural defects and shortcomings of existing technologies in the production of low-dielectric continuous basalt fibers from single ore raw materials, this invention provides an industrial preparation method that takes into account natural objective components, low dielectric properties, excellent mechanical properties, and high environmental friendliness. Summary of the Invention
[0006] To address the above problems, this invention provides a method for preparing low-dielectric continuous basalt fibers through multi-component raw material mixing and ceramic coating, the method comprising the following steps:
[0007] (1) Raw material selection: Select one or more neutral igneous rocks with a SiO2 mass percentage content greater than or equal to 56% and less than 66% and an alkali metal oxide (Na2O+K2O) mass percentage content less than or equal to 3.0% as the main material, and select one or more neutral igneous rocks with a SiO2 mass percentage content greater than or equal to 52% and less than 56% and an alkali metal oxide (Na2O+K2O) mass percentage content less than or equal to 3.0% as the auxiliary material;
[0008] (2) Raw material ratio: The chemical composition content of the main material and the auxiliary material selected in step (1) is determined by material testing methods. The ratio of the main material and the auxiliary material is determined by the target component content of the mixture. The target component content is as follows: SiO2 60-64%, Al2O3 14-18%, Fe2O3+FeO 6-8%, MgO 4-6%, CaO 5-7%, Na2O+K2O≤3.0%, TiO2 1.0-3.0%, and Fe2O3 / (Fe2O3+FeO)≥0.45;
[0009] (3) Mixing and processing: Mix, crush, grind, pass through an 80-100 mesh sieve, and homogenize the raw materials in the specified proportions to obtain a mixture. Sampling and testing are conducted to determine whether the actual component content of the mixture is within the target component content range.
[0010] (4) Oxidation control: Based on the ratio of Fe2O3 / (Fe2O3+FeO) in the actual composition of the mixture, determine whether to add or not to add an oxidizing agent: when Fe2O3 / (Fe2O3+FeO)≥0.85, no oxidizing agent is added; when Fe2O3 / (Fe2O3+FeO)<0.85, 0.1-5.0wt% of an oxidizing agent is added to make Fe2O3 / (Fe2O3+FeO)≥0.85 in the final fiber; the oxidizing agent is selected from one or more of NaNO3 and CeO2, and does not contain V2O5 or MnO2;
[0011] (5) Selection and addition of low dielectric functional oxides: Based on the actual composition and content of the compound and the expected dielectric properties of the continuous basalt fiber product, determine the type and amount of low dielectric functional oxides to be added;
[0012] (6) Secondary homogenization treatment: The low dielectric functional oxide and the oxidizing atmosphere agent are mixed with the mixture and homogenized, wherein the particle size of the low dielectric functional oxide and the oxidizing atmosphere agent is the same as that of the mixture, and a homogenized powder is obtained.
[0013] (7) Preparation of low dielectric ceramic phase wetting agent: According to the mass percentage, the following components are mixed evenly: 25-30% silica sol, 6-8% methyl phenyl silicone resin, 3-5% barium titanate nanoparticles, 2-3% nano silica, 3-4% titanate coupling agent, 2.5-3.5% γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), 1.5-2.5% γ-aminopropyltriethoxysilane (KH-550), 0.5-1.0% epoxy adhesion promoter, 0.3-0.5% ammonium polyacrylate dispersant, 0.1-0.2% nonionic fluorocarbon surfactant, 0.3-0.5% aluminum acetylacetonate, 0.05-0.10% glacial acetic acid, and the balance deionized water to prepare the wetting agent;
[0014] (8) Fiber drawing production: The homogenized powder obtained in step (6) is melted and drawn into fibers, and the sizing agent obtained in step (7) is used for impregnation and coating to obtain continuous basalt fibers;
[0015] The composition of the uncoated continuous basalt fibers obtained by drawing and forming meets the following requirements by mass percentage: SiO2 ≥ 52%; Al2O3 = 15%-18%; B2O3 = 2.0%-5.0%; TiO2 = 2.0%-4.0%; ZrO2 = 0.5%-3.0%; CeO2 = 0.5%-5.0%; Ho2O3 = 0.5%-5.0%; ZnO = 2.0%-4.0%; Y2O3 = 0.5-3.0%; total iron = 5%-8%; total alkali metal oxides (Na2O+K2O) ≤ 3.0%; Fe2O3 / (Fe2O3+FeO) ≥ 0.85; CaO = 4%-6%; MgO = 3%-5%; CaO+MgO = 7%-10%.
[0016] Furthermore, the neutral igneous rocks used as the main material include andesite or diorite; the neutral igneous rocks used as auxiliary materials include basalt, diabase, gabbro, basaltic andesite, or pyroxene andesite.
[0017] Furthermore, the mineral composition of the main material and the ingredients is dense or oblique porphyritic, and the ratio of Fe2O3 / (Fe2O3+FeO) is ≥0.45.
[0018] Furthermore, the target component content of the mixture mentioned in step (2) also includes, by mass percentage, the mineral composition: plagioclase ≥40%, pyroxene ≥20%, amphibole ≤25%, olivine ≤5%, quartz ≤15%; the chemical composition: SrO ≤0.3%, BaO ≤0.2%, Cl⁻ ≤0.15%; and the loss on ignition of the mixture ≤2.0%.
[0019] Furthermore, the amount of the oxidizing atmosphere agent added is 0.1-5.0 wt% (based on the mass percentage of the mixed ingredients). Those skilled in the art can select the amount of oxidizing atmosphere agent added based on the difference between the Fe2O3 / (Fe2O3+FeO) ratio and 0.85.
[0020] Furthermore, the low-dielectric functional oxide includes, but is not limited to, one or more of the following: network formers: SiO2, B2O3, Al2O3; network intermediates: TiO2, ZrO2, CeO2, Ho2O3; network modifiers: MgO, CaO.
[0021] Furthermore, the amount of the low dielectric functional oxide added can be 0-30% (by mass percentage of the mixture), such as 0-20%, 0-10%, etc. The specific amount added can be determined by those skilled in the art based on the actual content of the chemical composition of the mixture and the expected dielectric properties of the continuous basalt fiber product.
[0022] Furthermore, the preparation method of the low-dielectric ceramic phase wetting agent is as follows:
[0023] (a) Filler pretreatment: Barium titanate nanopowder and nano silica are placed in a vacuum oven and dried at 100-120℃ for 2-4 hours to remove physically adsorbed water on the particle surface and then cooled to room temperature for use.
[0024] (b) Preparation of coupling agent hydrolysate: Take a clean container, add 20-40% of the formula amount of deionized water, adjust the pH to 4.0-4.5 with glacial acetic acid, add all of the KH-560 and KH-550 silane coupling agents in the formula while stirring, and continue stirring for 25-35 minutes until the solution is completely transparent to obtain the coupling agent hydrolysate;
[0025] (c) Filler surface activation treatment: Take 40-60% of the formulation amount of titanate coupling agent, dilute with anhydrous ethanol (coupling agent: anhydrous ethanol = 1:2~4, volume ratio), spray the diluted titanate coupling agent solution evenly onto the surface of barium titanate nanopowder dried in step (a), stir and mix for 10-15 minutes, and then cure at 80-100℃ for 1-1.5 hours to obtain barium titanate nanopowder with titanate coupling agent surface activation; at the same time, mix the coupling agent hydrolysate prepared in step (b) with the dried nano silica powder at a solid-liquid ratio of 1:3~5, ultrasonically disperse for 20-30 minutes, and then dry and cure at 80-100℃ for 1-1.5 hours to obtain nano silica powder with silane coupling agent surface activation;
[0026] (d) Mixing of main ingredients: Add 30-50% of the total amount of deionized water to the mixing tank, and add silica sol, methyl phenyl silicone resin, the remaining coupling agent hydrolysate, polyacrylate ammonium salt dispersant and epoxy adhesion promoter in sequence while stirring. Stir at medium speed (400-600 rpm) for 10-15 minutes until uniform.
[0027] (e) Adding fillers: Add the surface-activated barium titanate nanoparticles and nano silica powders obtained in step (c) to the mixing tank, increase the stirring speed to 800-1000 rpm, disperse at high speed for 20-30 minutes, then add nonionic fluorocarbon surfactant and aluminum acetylacetonate, and continue stirring for 10 minutes.
[0028] (f) Conditioning and filtration: Add deionized water to the total amount of the formula, adjust the pH to 4.5-5.0 with glacial acetic acid, and filter with a 150-250 mesh stainless steel filter to obtain the low dielectric ceramic phase wetting agent.
[0029] Further, in step (8), the amount of sizing agent coated on the fiber surface is 0.8-1.5% of the fiber mass.
[0030] As used herein, the production of homogenized powder into fibers is carried out using conventional processes well known in the art, such as melting, fiber drawing, and impregnation coating. The impregnation coating is performed using the impregnating agent of this invention.
[0031] Furthermore, in step (8), the melting temperature is 1400-1480℃, the melt viscosity is controlled at 120-150Pa·s, and the wire drawing speed is 15-20 m / min.
[0032] Furthermore, the curing process of the impregnation coating is a two-stage curing process: the first stage is treated at 115-125℃ for 25-35 minutes, and the second stage is treated at 195-205℃ for 15-25 minutes. Alternatively, when the production line cannot meet the curing temperature of 200℃, the second stage is treated at 170-180℃ for 30-40 minutes.
[0033] In other respects, the present invention also provides low-dielectric continuous basalt fibers produced by the methods described herein.
[0034] Beneficial effects of the invention
[0035] 1) Significantly reduced dielectric constant: By ensuring SiO2 ≥ 52% to guarantee the integrity of the network skeleton, combined with a moderate content of Al2O3 (15-18%), a dense network structure of CaO (4-6%), MgO (3-5%), and CaO+MgO (7-10%), as well as precise control of B2O3 (2.0-5.0%) and the synergistic effect of CeO2 / Ho2O3, the dielectric constant (1MHz) can be reduced from 6.0-6.5 of ordinary basalt fiber to 3.8-4.5.
[0036] 2) The amount of B2O3 used is significantly lower than that of existing technologies, resulting in better environmental performance: The amount of B2O3 used (2.0-5.0%) is lower than the lower limit of 13.0 parts by weight of the comparative patent, which reduces boron volatilization pollution from the source.
[0037] 3) Effectively reduce dielectric loss: By screening low-alkali raw materials (Na2O+K2O≤3.0%) and precisely controlling Fe²⁺ / Fe³⁺ (Fe2O3 / (Fe2O3+FeO)≥0.85), the dielectric loss (1MHz) can be controlled between 0.0025-0.0045.
[0038] 4) Excellent balance between mechanical properties and manufacturability: The Al2O3 content is controlled within a moderate range of 15-18%, which ensures the density of the network structure and avoids the problems of excessively high melting temperature and difficult wire drawing caused by excessive aluminum content (>18%). The tensile strength can reach 2800-3000MPa and the elastic modulus can reach 85-92GPa.
[0039] 5) TiO2 content exceeds the upper limit of existing technology: TiO2 (2.0-4.0%) is higher than the upper limit of the comparative patent (2.0 parts by weight), utilizing Ti 4 ⁺High field strength reinforced network.
[0040] 6) Respect the characteristics of natural mineral composition: CaO (4-6%), MgO (3-5%), and CaO+MgO (7-10%) are all consistent with the actual composition characteristics of natural basalt fiber raw materials, avoiding "cutting the feet to fit the shoes" design. Detailed Implementation
[0041] To overcome the inherent limitations of producing low-dielectric continuous basalt fibers from a single ore source, while fully respecting and utilizing the objective compositional characteristics of natural basalt and ensuring industrial-scale production feasibility, this invention employs the following core technical means:
[0042] (1) Ensure SiO2 ≥ 52% to guarantee the integrity of the network skeleton: By selecting high-silicon natural minerals and mixing multiple components, ensure that SiO2 ≥ 52% in the final fiber, providing a solid structural foundation for low dielectric properties;
[0043] (2) Optimize Al2O3 content to 15-18%: Under the premise of ensuring high silicon content, control Al2O3 in a moderate range of 15-18%, which not only ensures the density of the network structure, but also avoids the problem of excessive melting temperature and difficulty in wire drawing caused by excessive aluminum content (>18%), thus achieving a balance between performance and manufacturability.
[0044] (3) Respect and utilize the potassium, sodium, calcium and magnesium content characteristics of natural ores: Natural ores have relatively high potassium, sodium, calcium and magnesium content. By blending multiple ores and adding low dielectric oxides and oxidizing atmosphere agents, the final secondary homogenized material for furnace feeding is controlled to K2O ≤0.5%, Na2O ≤2.5%, K2O+Na2O ≤3.0%; CaO is controlled at 4-6%, MgO at 3-5%, and CaO+MgO is maintained at 7-10%.
[0045] (4) Total iron content controlled at 5-8% and precise regulation of iron valence state: Iron is the essential characteristic element of basalt fiber. If its content is too low, it deviates from the material properties of basalt; if it is too high, it will introduce additional polarization loss. This invention controls the total iron (Fe2O3+FeO) within a moderate range of 5-8% by mixing multiple minerals. At the same time, by adding NaNO3+CeO2 composite oxidizing agent, Fe²⁺ is oxidized to Fe³⁺, so that Fe2O3 / (Fe2O3+FeO)≥0.85. The mechanism is that Fe²⁺ exists in the gaps of the glass network as an external body of the network, which destroys the continuity of the network structure and is prone to displacement polarization under an electric field, significantly increasing dielectric loss; while Fe³⁺ can partially enter the network to form [FeO4] tetrahedra to participate in the construction of the network skeleton, enhance the density and rigidity of the network structure, and effectively suppress ion migration and polarization loss. NaNO3 decomposes at high temperature to produce oxygen (2NaNO3→Na2O+2NO↑+O2↑). CeO2 works synergistically through redox reaction (2CeO2+2FeO→Ce2O3+Fe2O3) to achieve efficient conversion of Fe²⁺ to Fe³⁺, thereby effectively reducing dielectric loss caused by the presence of Fe²⁺.
[0046] (5) The amount of B2O3 used is significantly lower than that of the prior art: the amount of B2O3 added is controlled at 2.0-5.0% (lower than the lower limit of 13.0 parts by weight of the comparative patent), which significantly reduces the environmental pressure caused by boron volatilization;
[0047] (6) TiO2 content exceeds the upper limit of existing technology: TiO2 content is increased to 2.0-4.0% (higher than the upper limit of 2.0 parts by weight of the comparative patent), utilizing Ti 4 The high field strength of ⁺ further strengthens the network structure, indirectly reducing the dielectric properties of fiber products;
[0048] (7) Synergistic reduction of dielectric constant by rare earth oxides: CeO2 (0.5-5.0%) and Ho2O3 (0.5-5.0%) are introduced as rare earth functional oxides. Their synergistic effect can effectively reduce the dielectric constant and dielectric loss of the fiber. Among them, CeO2 participates in the regulation of iron valence state as an oxidizing agent (its oxidation reaction mechanism is described in Section (IV)). On the other hand, it enters the glass network together with Ho2O3, increasing the network disorder and suppressing polarization relaxation, thereby synergistically reducing the dielectric constant and dielectric loss.
[0049] (8) ZnO optimizes glass network structure and dielectric properties: Introducing ZnO (preferably 2.0-4.0%), at the optimal addition amount (preferably 4wt%), makes the glass network structure most connected, significantly reduces dielectric constant and dielectric loss, and at the same time reduces melt viscosity and improves the wire drawing process window;
[0050] (9) ZrO2 and Y2O3 network reinforcement and synergistic enhancement: ZrO2 (preferably 1.0-3.0%) and Y2O3 (preferably 0.5-3.0%) are introduced as network intermediates and structural reinforcement components. The ratio of the two to Al2O3 satisfies (ZrO2+Y2O3) / Al2O3=0.15-0.50, and the total amount does not exceed 50% of the Al2O3 content. Among them, ZrO2 has high field strength characteristics, which can effectively strengthen the network skeleton and improve the mechanical properties and chemical stability of the fiber; Y2O3, as a rare earth oxide, can enter the crystal lattice to form a solid solution, enhance the rigidity of the network, and produce a synergistic dielectric reduction effect with CeO2 / Ho2O3, further improving the comprehensive performance of the fiber.
[0051] (10) Synergistic Dielectric Reduction by Low-Dielectric Ceramic Phase Wetting Agent: A low-dielectric ceramic phase wetting agent is coated on the fiber surface. After curing, a SiO2-TiO2-BaTiO3 composite low-dielectric protective structure is formed on the fiber surface. This wetting agent uses silica sol as the matrix and nano-silica as the main functional filler. The coating itself has a low dielectric constant and dielectric loss, and can effectively repair fiber surface defects and suppress interfacial polarization. It forms a synergistic effect with the low dielectric properties of the fiber body, further reducing the dielectric constant and dielectric loss of the fiber. The amount of wetting agent coated is controlled to be 0.8-1.5% of the fiber mass.
[0052] The present invention will be further illustrated below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in this technical field.
[0053] Example:
[0054] This invention provides a method for preparing low-dielectric continuous basalt fibers by multi-component raw material mixing and ceramic coating, comprising:
[0055] (1) Raw material selection: In order to achieve the goal of low alkali, this embodiment selects low alkali andesite / diorite as the main material and low alkali basaltic andesite as the auxiliary material. See Table 1 for details.
[0056] Table 1: Mineral Points for Blending Multi-component Raw Materials
[0057]
[0058] (2) Determine the chemical composition content of each of the mixed ores: the results are shown in Table 2, where LOI is the measured loss on ignition.
[0059] Table 2: Chemical composition of each blended ore (wt%)
[0060]
[0061] (3) Batching: Based on the target content, calculate the wt% of each ore in the blend according to the chemical composition of each ore in Table 2. The results are shown in Table 3. Weigh 65 parts of No. 1 main material, 30 parts of No. 2 main material, and 5 parts of No. 3 batching material according to wt% and blend them. The comparative example uses low-alkali basaltic andesite as the single ore material.
[0062] Table 3: Weight percentage of blended ores (wt%)
[0063]
[0064] (4) Mixing test: The mixtures from Examples 1-5 were crushed, ground, and sieved (80-100 mesh) and then sampled for testing to ensure that the content of each component in the mixture was within the required range (if the requirements were not met, secondary mixing was required) to obtain the mixed powder. The test results of the content of each chemical component in the mixtures obtained from Examples 1-5 and the minerals of the comparative example are shown in Table 4.
[0065] Table 4: Content of each component after ore blending (wt%)
[0066]
[0067] (5) Oxidation control: Based on the Fe2O3 / (Fe2O3+FeO) ratio of the mixtures in Examples 1-5 being 0.58 (<0.85), 0.5% NaNO3 + 4% CeO2 composite oxidizing agent was added to the mixtures in all examples, so that the Fe2O3 / (Fe2O3+FeO) ratio in the final fiber was ≥0.85. No V2O5 or MnO2 was added in any of the examples. The specific amounts added are shown in Table 5.
[0068] (6) Selection and addition of low dielectric oxides: Based on the content of each major chemical component in the mixture, low dielectric oxides (wt%) as listed in Table 5 were added to the mixtures of Examples 1-5. The determined low dielectric functional oxides and oxidizing atmosphere agents were included in the secondary homogenization treatment in step (7).
[0069] Table 5: Additive dosage in each embodiment (wt%, based on 100 parts of the mixture)
[0070]
[0071] (7) Secondary homogenization treatment: The low dielectric functional oxide and oxidizing atmosphere agent are mixed with the compound and homogenized to obtain homogenized powder, wherein the particle size of the added low dielectric functional oxide and oxidizing atmosphere agent is the same as that of the compound.
[0072] (8) Formulation of low-dielectric ceramic phase wetting agent: see Table 6. The preparation method of the low-dielectric ceramic phase wetting agent is as follows:
[0073] (a) Filler pretreatment: Barium titanate nanopowder and nano silica are placed in a vacuum oven and dried at 100-120℃ for 2-4 hours to remove physically adsorbed water on the particle surface and then cooled to room temperature for use.
[0074] (b) Preparation of coupling agent hydrolysate: Take a clean container, add 20-40% of the formula amount of deionized water, adjust the pH to 4.0-4.5 with glacial acetic acid, slowly add all of the KH-560 and KH-550 silane coupling agents in the formula while stirring, and continue stirring for 25-35 minutes until the solution is completely transparent to obtain the coupling agent hydrolysate;
[0075] (c) Filler surface activation treatment: Take 40-60% of the formulation amount of titanate coupling agent (NDZ-201), dilute with anhydrous ethanol (coupling agent: anhydrous ethanol = 1:2~4, volume ratio), spray the diluted titanate coupling agent solution evenly onto the surface of the barium titanate nanopowder dried in step (a), stir and mix at high speed for 10-15 minutes, and then cure at 80-100℃ for 1-1.5 hours to obtain barium titanate powder with titanate coupling agent surface activation; at the same time, mix the coupling agent hydrolysate prepared in step (b) with the dried nano silica powder at a solid-liquid ratio of 1:3~5, ultrasonically disperse for 20-30 minutes, and then dry and cure at 80-100℃ for 1-1.5 hours to obtain nano silica powder with silane coupling agent surface activation;
[0076] (d) Mixing of main ingredients: Add 30-50% of the total amount of deionized water to the mixing tank, and add silica sol, methyl phenyl silicone resin, coupling agent hydrolysate (remaining part), polyacrylate ammonium salt dispersant and epoxy adhesion promoter in sequence while stirring. Stir at medium speed (400-600 rpm) for 10-15 minutes until uniform.
[0077] (e) Adding fillers: Slowly add the surface-activated barium titanate nanopowder and nano silica powder obtained in step (c) into the mixing tank, increase the stirring speed to 800-1000 rpm, disperse at high speed for 20-30 minutes, then add nonionic fluorocarbon surfactant and aluminum acetylacetonate, and continue stirring for 10 minutes.
[0078] (f) Conditioning and filtration: Add deionized water to the total amount of the formula, adjust the pH to 4.5-5.0 with glacial acetic acid, and filter with a 150-250 mesh stainless steel filter to obtain the low dielectric ceramic phase wetting agent.
[0079] Table 6: Formulation of Low Dielectric Ceramic Phase Wetting Agent Coating (wt%)
[0080]
[0081] (9) Wire drawing production: Wire drawing production is carried out using a process of melting, wire drawing, and impregnation coating. The homogenized powder obtained in step (7) is used for melting and wire drawing, and the impregnating agent prepared in step (8) is used for impregnation coating as a coating. The melting process parameters are: temperature 1400-1480℃, melt viscosity controlled at 120-150 Pa·s, and wire drawing speed 15-20 m / min; the coating curing process is a two-stage curing: the first stage is treated at 115-125℃ for 25-35 min, and the second stage is treated at 195-205℃ for 15-25 min.
[0082] (10) Performance testing: The prepared continuous basalt fibers were tested. The main test items included the dielectric constant, dielectric loss tangent, tensile strength, tensile modulus, etc. The test results are shown in Table 7.
[0083] Table 7: Final composition and properties of continuous basalt fibers prepared in each example
[0084]
[0085]
[0086] *Note: Fe2O3 / (Fe2O3+FeO) is the mass ratio. The values in the table are calculated directly based on the mass fractions of Fe2O3 and FeO.
[0087] As can be seen from the data in Table 7:
[0088] Dielectric constant: Compared to comparative example (6.2), the dielectric constant of all examples was significantly reduced. From Example 1 to Example 5, the dielectric constant gradually increased from 4.0 to 4.8 as the amount of B2O3 added (3.31% → 1.69%) gradually decreased. The dielectric constants of Examples 1-3 were 4.0, 4.2, and 4.4, respectively, all meeting the target range of 3.8-4.5; Examples 4 (4.6) and 5 (4.8) were slightly higher than the upper limit of the target. This indicates that B2O3 is the core component for reducing the dielectric constant, and optimal low dielectric performance can be obtained by controlling it within the range of 2.5-4.0%.
[0089] Dielectric loss: Compared to the comparative example (0.015), the dielectric loss tangent of all embodiments was significantly reduced. From Example 1 to Example 5, the dielectric loss gradually increased from 0.0031 to 0.0043, and all embodiments met the target requirement of ≤0.005. This is due to:
[0090] The low-alkali raw material screening strategy ensures that the final fiber contains ≤2.67% Na2O+K2O, effectively suppressing the loss contribution caused by the relaxation polarization of alkali metal ions.
[0091] The precise control of Fe²⁺ / Fe³⁺ by the oxidizing atmosphere agent (NaNO3+CeO2) which does not contain V₂O₅ or MnO₂ increases the Fe₂O₃ / (Fe₂O₃+FeO) ratio from 0.58 in the mixture to 0.884, achieving the target requirement of ≥0.85.
[0092] The aluminum-oxygen tetrahedra formed by Al2O3 (15.99-16.26%) effectively bind the migration of alkali metal ions;
[0093] Synergistic dielectric reduction effect of B2O3 and CeO2 / Ho2O3.
[0094] Tensile strength and tensile modulus of elasticity: Compared with the comparative example, the tensile strength and tensile modulus of elasticity of all embodiments were significantly improved. From Example 1 to Example 5, the tensile strengths were 2920 MPa, 3000 MPa, 2950 MPa, 2870 MPa, and 2790 MPa, respectively, and the tensile modulus of elasticity were 87.2 GPa, 89.2 GPa, 87.7 GPa, 85.7 GPa, and 84.2 GPa, respectively. Among them, Example 2 had the highest tensile strength (3000 MPa) and tensile modulus of elasticity (89.2 GPa), which was attributed to its moderate B2O3 content (2.91%) and high Al2O3 content (16.06%), achieving the best balance between network structure and mechanical properties.
[0095] Trend analysis between implementation examples:
[0096] Relationship between B2O3 content and dielectric properties: From Example 1 to Example 5, the B2O3 content decreased from 3.31% to 1.69%, the dielectric constant increased from 4.0 to 4.8, the dielectric loss increased from 0.0031 to 0.0043, and the melting temperature increased from 1436℃ to 1488℃. This indicates that B2O3 can not only effectively reduce the dielectric constant and dielectric loss, but also significantly reduce the melting temperature and broaden the wire drawing process window. However, excessive B2O3 will reduce mechanical properties. In Example 2, the B2O3 content was 2.91%, achieving the best balance between dielectric properties, mechanical properties, and process performance.
[0097] The optimization effect of Al2O3 content: The Al2O3 content increased from 15.99% in Example 1 to 16.26% in Example 5, both approaching or reaching the target range of 16-18%. The Al2O3 content (16.06-16.26%) in Examples 2-5 were all within the target range, ensuring the compactness of the network skeleton.
[0098] Synergistic effect of ZnO, ZrO2, and Y2O3: In all embodiments, the (ZnO+ZrO2+Y2O3) / Al2O3 ratio remained stable between 0.28 and 0.30 (0.284 in Example 1 and 0.295 in Example 5), meeting the target range of 0.15-0.50. ZnO (2.06-2.09%) optimized the network structure and reduced melt viscosity; ZrO2 (1.64-1.67%) strengthened the network skeleton; and Y2O3 (0.82-0.84%) enhanced network rigidity. The synergistic ratio of these three components with Al2O3 enabled the fiber to achieve excellent mechanical properties while maintaining low dielectric properties.
[0099] Precise control of iron valence state by oxidizing atmosphere agent: By adding a composite oxidizing atmosphere agent of 0.5% NaNO3 + 4.0% CeO2, the Fe2O3 / (Fe2O3 + FeO) ratio significantly increased from 0.58 (mass ratio, molar ratio approximately 0.40) in the mixture to 0.884 (mass ratio, molar ratio approximately 0.65) in the final fiber. NaNO3 decomposes at high temperature to produce oxygen, oxidizing some Fe²⁺ to Fe³⁺; CeO2, as an oxidant, also participates in the reaction, further oxidizing the remaining Fe²⁺. Stoichiometric calculations show that 0.5% NaNO3 oxidizes 0.423 parts of FeO, and 4.0% CeO2 oxidizes 1.672 parts of FeO, for a total oxidation of 2.095 parts of FeO, reducing FeO from the initial 2.92 parts to 0.825 parts, while simultaneously generating 2.328 parts of Fe2O3, increasing Fe2O3 from the initial 3.97 parts to 6.298 parts. This precise regulation effectively reduced the additional polarization loss caused by Fe²⁺ as the network outer layer, playing a key role in reducing dielectric loss. Simultaneously, the Na₂O (approximately 0.365 parts) introduced by NaNO₃ decomposition controlled the final Na₂O content at 2.24-2.28%. Combined with K₂O (0.39%), the total Na₂O + K₂O content was controlled at 2.63-2.67%, meeting the low-alkali requirement of ≤3.0%.
[0100] Oxidation effect of Fe2O3 / (Fe2O3+FeO): The final Fe2O3 / (Fe2O3+FeO) ratio in each embodiment was stable at 0.884, which is higher than the target requirement of 0.85, proving the effectiveness and stability of the oxidation control strategy.
[0101] Verification by the comparative example: The comparative example used low-alkali basaltic andesite (Na2O+K2O=2.92%, CaO+MgO=14.00%). Although it underwent the same fiber body additive treatment and optimized ceramic coating, its dielectric constant (6.2) and dielectric loss (0.015) were still much higher than all the examples. This fully demonstrates the core contribution of the present invention to reducing dielectric performance through fiber body modification methods such as low-alkali raw material screening, precise control of B2O3, and precise regulation of iron valence state. It also verifies the synergistic effect of the optimized ceramic coating on dielectric performance.
[0102] In summary, by ensuring a final SiO2 ≥ 52%, Al2O3 controlled at 16-18%, CaO+MgO maintained at 7-10%, and B2O3 (2.0-5.0%) precisely controlled and combined with ZnO, ZrO2, and Y2O3 for synergistic enhancement, and by precisely controlling the iron valence state with an oxidizing agent free of V2O5 and MnO2 (making Fe2O3 / (Fe2O3+FeO) ≥ 0.85), the dielectric properties of continuous basalt fibers have been systematically optimized. The dielectric constant can be as low as 4.0, the dielectric loss as low as 0.0031, and the tensile strength as high as 3000 MPa, achieving synergistic optimization of low dielectric properties and excellent mechanical properties.
[0103] The continuous basalt fibers prepared in all embodiments of the present invention have the following advantages compared with basalt fibers prepared using low-alkali basaltic andesite as a single mineral.
[0104] (i) Extremely low dielectric constant. The continuous basalt fibers prepared in Examples 1-5 have dielectric constants ranging from 4.0 to 4.8 at a frequency of 1MHz. Among them, Examples 1-3 (4.0-4.4) meet the target requirement of 3.8-4.5, which is much lower than the comparative example of 6.2. This meets the requirements for the use of low dielectric reinforcement materials in high-frequency and high-speed printed circuit boards, and is comparable to the level of 3.89-4.07 in the comparative patent CN202210684757.
[0105] (ii) Extremely low dielectric loss. The continuous basalt fibers prepared in Examples 1-5 exhibited excellent dielectric stability with a dielectric loss tangent of 0.0031-0.0043 at 1 MHz, significantly lower than the 0.015 of the comparative example. The dielectric loss was further reduced by precisely controlling the iron valence state (Fe2O3 / (Fe2O3+FeO) increased from 0.58 to 0.884) using an oxidizing agent free of V2O5 and MnO2.
[0106] (III) Achieving excellent low dielectric properties with a B2O3 content far lower than that of existing technologies. Compared with the comparative patent CN202210684757, the B2O3 content of this invention (2.0-5.0%) is far lower than the 13-23 parts by weight of that patent, a reduction of 60-85%. While significantly reducing raw material costs and the environmental pressure of boron volatilization, it achieves equally excellent low dielectric properties (dielectric constant 4.0-4.4), and this invention also has superior mechanical properties (tensile strength up to 3000MPa).
[0107] (iv) Excellent mechanical properties. Through high Al2O3 (16-18%) network reinforcement and multi-component synergistic reinforcement of ZnO, ZrO2 and Y2O3, the fiber of this invention can achieve a tensile strength of 2790-3000MPa and a tensile elastic modulus of 84.2-89.2GPa while maintaining low dielectric properties, which is superior to the mechanical properties of existing low dielectric basalt fibers.
[0108] (v) It has a process window that allows for industrial production. The melting temperature is 1436-1488℃, the forming temperature is 1296-1348℃, the liquidus temperature is 1156-1208℃, and the drawing window ΔT reaches 140℃, which is far greater than the basic requirement of 50℃. All of these are within the feasible range for industrial production, which is conducive to energy conservation and process control.
[0109] (vi) The high filament yield and full barrel rate ensured the economic benefits of production. The filament yield was 87.0-89.0%, and the full barrel rate was 89.0-91.0%, which was far better than the comparative ratio of 81.0% and 27.4%.
[0110] It should be noted that while the preferred embodiments of the present invention are provided in this specification, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. These embodiments are not intended to impose additional limitations on the content of the present invention; their purpose is to provide a more thorough and comprehensive understanding of the disclosure of the present invention. Furthermore, the above-described technical features can be combined with each other to form various embodiments not listed above, all of which are considered to be within the scope of the present invention. Moreover, those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.
Claims
1. A method for preparing low-dielectric continuous basalt fibers by multi-component raw material mixing and ceramic coating, characterized in that, The method includes the following steps: (1) Raw material selection: Select one or more neutral igneous rocks with a SiO2 mass percentage content greater than or equal to 56% and less than 66% and an alkali metal oxide (Na2O+K2O) mass percentage content less than or equal to 3.0% as the main material, and select one or more neutral igneous rocks with a SiO2 mass percentage content greater than or equal to 52% and less than 56% and an alkali metal oxide (Na2O+K2O) mass percentage content less than or equal to 3.0% as the auxiliary material; (2) Raw material ratio: The chemical composition content of the main material and the auxiliary material selected in step (1) is determined by material testing methods. The ratio of the main material and the auxiliary material is determined by the target component content of the mixture. The target component content is as follows: SiO2 60-64%, Al2O3 14-18%, Fe2O3+FeO 6-8%, MgO 4-6%, CaO 5-7%, Na2O+K2O≤3.0%, TiO2 1.0-3.0%, and Fe2O3 / (Fe2O3+FeO)≥0.45; (3) Mixing and processing: Mix, crush, grind, pass through an 80-100 mesh sieve, and homogenize the raw materials in the specified proportions to obtain a mixture. Sampling and testing are conducted to determine whether the actual component content of the mixture is within the target component content range. (4) Oxidation control: Based on the ratio of Fe2O3 / (Fe2O3+FeO) in the actual composition of the mixture, determine whether to add or not to add an oxidizing agent: when Fe2O3 / (Fe2O3+FeO)≥0.85, no oxidizing agent is added; when Fe2O3 / (Fe2O3+FeO)<0.85, 0.1-5.0wt% of an oxidizing agent is added to make Fe2O3 / (Fe2O3+FeO)≥0.85 in the final fiber; the oxidizing agent is selected from one or more of NaNO3 and CeO2, and does not contain V2O5 or MnO2; (5) Selection and addition of low dielectric functional oxides: The low dielectric functional oxides are selected from one or more of the following: 1) Network forming body: SiO2, B2O3, Al2O3; 2) Network intermediate: TiO2, ZrO2, CeO2, Ho2O3, Y2O3, ZnO; 3) Network altering body: MgO, CaO. The type and amount of low dielectric functional oxides to be added are determined according to the actual composition and content of the mixture and the expected dielectric properties of the continuous basalt fiber product. (6) Secondary homogenization treatment: The low dielectric functional oxide and the oxidizing atmosphere agent are mixed with the mixture and homogenized, wherein the particle size of the low dielectric functional oxide and the oxidizing atmosphere agent is the same as that of the mixture, and a homogenized powder is obtained. (7) Preparation of low dielectric ceramic phase wetting agent: According to the mass percentage, 25-30% silica sol, 6-8% methyl phenyl silicone resin, 3-5% barium titanate nanopowder, 2-3% nano silica, 3-4% titanate coupling agent, 2.5-3.5% γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 1.5-2.5% γ-aminopropyltriethoxysilane, 0.5-1.0% epoxy adhesion promoter, 0.3-0.5% ammonium polyacrylate dispersant, 0.1-0.2% nonionic fluorocarbon surfactant, 0.3-0.5% aluminum acetylacetonate, 0.05-0.10% glacial acetic acid and the balance deionized water are mixed evenly to prepare the wetting agent; (8) Fiber drawing production: The homogenized powder obtained in step (6) is melted and drawn into fibers, and the sizing agent obtained in step (7) is used for impregnation and coating to obtain continuous basalt fibers; The composition of the uncoated continuous basalt fibers obtained by drawing and forming meets the following requirements by mass percentage: SiO2 ≥ 52%; Al2O3 = 15%-18%; B2O3 = 2.0%-5.0%; TiO2 = 2.0%-4.0%; ZrO2 = 0.5%-3.0%; CeO2 = 0.5%-5.0%; Ho2O3 = 0.5%-5.0%; ZnO = 2.0%-4.0%; Y2O3 = 0.5-3.0%; total iron = 5%-8%; total alkali metal oxides (Na2O+K2O) ≤ 3.0%; Fe2O3 / (Fe2O3+FeO) ≥ 0.85; CaO = 4%-6%; MgO = 3%-5%; CaO+MgO = 7%-10%.
2. The method according to claim 1, characterized in that, The main neutral igneous rocks include andesite or diorite; the auxiliary neutral igneous rocks include basalt, diabase, gabbro, basaltic andesite, or pyroxene andesite.
3. The method according to claim 1, characterized in that, The mineral composition of the main ingredients and auxiliary ingredients is dense or oblique porphyritic, and the ratio of Fe2O3 / (Fe2O3+FeO) is ≥0.
45.
4. The method according to claim 1, characterized in that, The target component content of the mixture mentioned in step (2) also includes: SrO≤0.3%, BaO≤0.2%, Cl⁻≤0.15%; and the loss on ignition of the mixture ≤2.0%.
5. The method according to claim 1, characterized in that, The preparation method of the low-dielectric ceramic phase wetting agent is as follows: (a) Filler pretreatment: Barium titanate nanopowder and nano silica are placed in a vacuum oven and dried at 100-120℃ for 2-4 hours to remove physically adsorbed water on the particle surface and then cooled to room temperature for use. (b) Preparation of coupling agent hydrolysate: Take a clean container, add 20-40% of the formula amount of deionized water, adjust the pH to 4.0-4.5 with glacial acetic acid, add all of the KH-560 and KH-550 silane coupling agents in the formula while stirring, and continue stirring for 25-35 minutes until the solution is completely transparent to obtain the coupling agent hydrolysate; (c) Filler surface activation treatment: Take 40-60% of the formulation amount of titanate coupling agent, dilute with anhydrous ethanol (coupling agent: anhydrous ethanol = 1:2~4, volume ratio), spray the diluted titanate coupling agent solution evenly onto the surface of barium titanate nanopowder dried in step (a), stir and mix for 10-15 minutes, and then cure at 80-100℃ for 1-1.5 hours to obtain barium titanate nanopowder with titanate coupling agent surface activation; at the same time, mix the coupling agent hydrolysate prepared in step (b) with the dried nano silica powder at a solid-liquid ratio of 1:3~5, ultrasonically disperse for 20-30 minutes, and then dry and cure at 80-100℃ for 1-1.5 hours to obtain nano silica powder with silane coupling agent surface activation; (d) Mixing of main ingredients: Add 30-50% of the total amount of deionized water to the mixing tank, and add silica sol, methyl phenyl silicone resin, the remaining coupling agent hydrolysate, polyacrylate ammonium salt dispersant and epoxy adhesion promoter in sequence while stirring. Stir at medium speed (400-600 rpm) for 10-15 minutes until uniform. (e) Adding fillers: Add the surface-activated barium titanate nanoparticles and nano silica powders obtained in step (c) to the mixing tank, increase the stirring speed to 800-1000 rpm, disperse at high speed for 20-30 minutes, then add nonionic fluorocarbon surfactant and aluminum acetylacetonate, and continue stirring for 10 minutes. (f) Conditioning and filtration: Add deionized water to the total amount of the formula, adjust the pH to 4.5-5.0 with glacial acetic acid, and filter with a 150-250 mesh stainless steel filter to obtain the low dielectric ceramic phase wetting agent.
6. The method according to claim 1, characterized in that, The amount of sizing agent applied to the fiber surface in step (8) is 0.8-1.5% of the fiber mass.
7. The method according to claim 1, characterized in that, In step (8), the melting temperature is 1400-1480℃, the melt viscosity is controlled at 120-150Pa·s, and the wire drawing speed is 15-20 m / min.
8. The method according to claim 1, characterized in that, The curing process of the impregnation coating is a two-stage curing process: the first stage is treated at 115-125℃ for 25-35 minutes, and the second stage is treated at 170-180℃ for 30-40 minutes or at 195-205℃ for 15-25 minutes.
9. A low-dielectric continuous basalt fiber produced by the method of any one of claims 1-8.
Citation Information
Patent Citations
A corrosion-resistant, low-dielectric basalt fiber, its preparation method, and a high-frequency, high-speed printed circuit board.
CN115093124B